2023
DOI: 10.1177/02683962231164426
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in transfer, translation, and transformation of information: A sociomaterial perspective on heterogeneous work arrangements

Abstract: Although sociomaterial theorizing has provided important insights into how digital technologies enable or constrain behavior in organizational contexts, there is a need to advance theory to better account for how digital technologies shape heterogeneous work practices in which distributed organizational actors use diverse technology portfolios to collaboratively produce and consume information. Against that backdrop, we draw on the distinction between digital mediation and digital representation to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Expanding the focus of the MOT construct, it permits the conduction of the exploration at the connection between security objectives and compliance methodologies, bringing scholarly attention to these intersections as documented by Sulaiman et al (2022). By foregrounding the multifaceted roles that motivation plays in shaping behavioral outcomes, the construct offers a more sophisticated understanding of the mechanisms through which organizational interventions and managerial orchestrations geared towards enhancing employee motivation can galvanize collective adherence to prescribed security frameworks, as suggested in Ballet et al ( 2011) and, more recently confirmed by Mathiassen et al (2023), and by Klemsdal and Wittusen (2023).…”
Section: Construct Motmentioning
confidence: 92%
See 1 more Smart Citation
“…Expanding the focus of the MOT construct, it permits the conduction of the exploration at the connection between security objectives and compliance methodologies, bringing scholarly attention to these intersections as documented by Sulaiman et al (2022). By foregrounding the multifaceted roles that motivation plays in shaping behavioral outcomes, the construct offers a more sophisticated understanding of the mechanisms through which organizational interventions and managerial orchestrations geared towards enhancing employee motivation can galvanize collective adherence to prescribed security frameworks, as suggested in Ballet et al ( 2011) and, more recently confirmed by Mathiassen et al (2023), and by Klemsdal and Wittusen (2023).…”
Section: Construct Motmentioning
confidence: 92%
“…We argue that the enhanced research model benefits from including aspects like managerial behaviours, isomorphism, response variations, and compliance incentives. By assimilating these, the model offers a comprehensive view of the dynamics governing compliance behaviour, showcasing the intricate relationship between organisational processes, external standards, managerial influence, individual perceptions, and motivational elements, Hina et al (2019), Mathiassen et al (2023).…”
Section: The Proposed Modelmentioning
confidence: 99%
“…Despite their potential to enrich organisation-level studies, micro dynamics remain largely unexplored in the digital transformation literature. Adopting a multi-IS paradigm (Gerlach & Cenfetelli, 2022) is one approach that acknowledges the diverse sets of digital technologies individuals use in their work-life (Mathiassen et al, 2023). Furthermore, empirical data from the Global South, which would contribute to the scientific discourse on digital transformation, is frequently disregarded (Elbanna & Idowu, 2022).…”
Section: A Micro-level Perspective On Digital Transformationmentioning
confidence: 99%
“…Additionally, case studies that focus on organisational outcomes through macro-level investigations often adhere to a single-IS paradigm (Gerlach & Cenfetelli, 2022), failing to capture the diverse array of digital technologies individuals use both for work and leisure (Mathiassen et al, 2023;Vaast & Pinsonneault, 2022). Furthermore, the existing digital transformation literature appears to presume that those tasked with implementing strategic decisions about the use of digital technologies possess the requisite skills, resources, and socio-economic status (Virtaneva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The diverse and interconnected nature of the digital world necessitates a nuanced approach to ethics, one that comprehensively understands and respects the cultural variances in perception and values. Issues such as data privacy, digital rights, and the ethical use of artificial intelligence (AI) must be viewed and addressed through a multicultural lens to ensure fairness and respect for all cultures (442,443). Data privacy, a cornerstone of digital ethics, varies significantly across cultural contexts.…”
Section: Ethical Considerations In a Multicultural Digital Worldmentioning
confidence: 99%